2022
DOI: 10.3390/biomedicines10020513
|View full text |Cite
|
Sign up to set email alerts
|

Single Application of Low-Dose, Hydroxyapatite-Bound BMP-2 or GDF-5 Induces Long-Term Bone Formation and Biomechanical Stabilization of a Bone Defect in a Senile Sheep Lumbar Osteopenia Model

Abstract: Effects of hydroxyapatite (HA) particles with bone morphogenetic BMP-2 or GDF-5 were compared in sheep lumbar osteopenia; in vitro release in phosphate-buffered saline (PBS) or sheep serum was assessed by ELISA. Lumbar (L) vertebral bone defects (Ø 3.5 mm) were generated in aged, osteopenic female sheep (n = 72; 9.00 ± 0.11 years; mean ± SEM). Treatment was: (a) HA particles (2.5 mg; L5); or (b) particles coated with BMP-2 (1 µg; 10 µg) or GDF-5 (5 µg; 50 µg; L4; all groups n = 6). Untouched vertebrae (L3) ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 82 publications
(163 reference statements)
1
12
0
Order By: Relevance
“…We found that butyl flufenamate ointment and FFA promoted BMP2 secretion in mSMSCs both in vivo and in vitro. Butyl flufenamate ointment and FFA are generally believed to play an anti-inflammatory role [ 26 , 27 , 28 ]; we are the first to show that they can induce mSMSCs to secrete the key osteogenic factor BMP2 [ 29 , 30 , 31 ]. Although the mechanism of action by which the topical application of butyl flufenamate ointment accelerates healing of cranial defects in mice has not been completely elucidated, it is mediated by promoting BMP2 secretion in mSMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that butyl flufenamate ointment and FFA promoted BMP2 secretion in mSMSCs both in vivo and in vitro. Butyl flufenamate ointment and FFA are generally believed to play an anti-inflammatory role [ 26 , 27 , 28 ]; we are the first to show that they can induce mSMSCs to secrete the key osteogenic factor BMP2 [ 29 , 30 , 31 ]. Although the mechanism of action by which the topical application of butyl flufenamate ointment accelerates healing of cranial defects in mice has not been completely elucidated, it is mediated by promoting BMP2 secretion in mSMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the cylinders were coated with recombinant human BMP-2 (rhBMP-2; 25 and 250 µg) or rhGDF-5 (125 and 1250 µg) by application of the BMP-containing solutions on the cylinders and subsequent sterile drying in circulating air at room temperature (Table 1 ; [ 49 ]). In brief, non-glycosylated BMP-2 was produced in E. coli using patented procedures (patent DE 199 44 626 A1; [ 49 ] and references therein) also commonly used for clinical trials in humans, GDF-5 by analogous procedures. The present dosages were chosen on the basis of BMP doses successfully applied in previous experiments with BMP-coated hydroxyapatite-titanium tibia implants [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Calculating the surface area required for single layer binding of BMP-2 or GDF-5, the loading protein should have been completely immobilized on the surface of the CP cylinders. Although the release kinetics of the loaded protein were not formally analyzed, an almost complete cumulative release of the surface-coated BMPs from the CP cylinders in serum within 14 days can be assumed on the basis of previous results from HA-particles ([ 49 ] and references therein).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP-2 is one of the most important osteogenic growth factors in the BMP family. It has been applied for clinical fracture therapy and its ability to promote osteogenic differentiation of MSC has been demonstrated in many studies ( Lo et al, 2012 ; Hasenbein et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%